Synthesis and Characterization of 2-Arylbenzimidazoles by Reaction of o-Nitroaniline and Aromatic Aldehyde Derivatives via Reductive Cyclization - IBRAHIM, M.N. (Asian Journal of Chemistry, 2010)
The synthesis of several 2-substituted benzimidazole derivatives was achieved via reduction of o-nitroaniline in presence of aromatic aldehydes with sodium dithionite. The derivatives were characterized by physical and spectral analysis.